Noncoding RNA in the transcriptional landscape of human neural progenitor cell differentiation - Hecht, Patrick M.; Ballesteros-Yanez, Inmaculada; Grepo, Nicole; Knowles, James A.; Campbell, Daniel B. (Frontiers in Neuroscience, 2015)
Increasing evidence suggests that noncoding RNAs play key roles in cellular processes, particularly in the brain. The present study used RNA sequencing to identify the transcriptional landscape of two human neural progenitor cell lines, SK-N-SH and ReNcell CX, as they differentiate into human cortical projection neurons. Protein coding genes were found to account for 54.8% and 57.0% of expressed genes, respectively, and alignment of RNA sequencing reads revealed that only 25.5-28.1% mapped to exonic regions of the genome. Differential expression analysis in the two cell lines identified altered gene expression in both protein coding and noncoding RNAs as they undergo neural differentiation with 222 differentially expressed genes observed in SK-N-SH cells and 19 differentially expressed genes in ReNcell CX. Interestingly, genes showing differential expression in SK-N-SH cells are enriched in genes implicated in autism spectrum disorder, but not in gene sets related to cancer or Alzheimer’s disease. Weighted gene co-expression network analysis (WGCNA) was used to detect modules of co-expressed protein coding and noncoding RNAs in SK-N-SH cells and found four modules to be associated with neural differentiation. These modules contain varying levels of noncoding RNAs ranging from 10.7% to 49.7% with gene ontology suggesting roles in numerous cellular processes important for differentiation. These results indicate that noncoding RNAs are highly expressed in human neural progenitor cells and likely hold key regulatory roles in gene networks underlying neural differentiation and neurodevelopmental disorders.